PENGARUH PERILAKU BIROKRASI TERHADAP KUALITAS PELAYANAN PUBLIK DI SAMSAT KOTA GORONTALO - Sri Ramla Dali; Ismet Sulila; Juriko Abdussamad (Journal Education and Government Wiyata, 2024)
Indonesia's Public services frequently encounter challenges, such as a lack of dedication and poor service quality. This study aimed to determine the influence of bureaucratic behavior on the quality of public services in the One-stop Administration Service Office of Gorontalo City. This quantitative research used a descriptive method and a referential approach applied to 34 samples. This study used validity and reliability tests to examine the instrument. The data analysis techniques used were normality test, determinant coefficient (R), t-test, and simple linear regression analysis with SPSS 26 software. Based on the analysis, the t-count test was 11.962, and the t-table was 2.036. This result indicated that He was rejected and H, was confirmed, or there was a significant influence between bureaucratic behavior and the quality of public services in the One-stop Administration Service Office of Gorontalo City. Further, the determinant coefficient (R2) test obtained 0.817, which meant bureaucratic behavior (independent variable or X) influenced 81.7% of the quality of public services (dependent variable or Y). The other 18.3% of the results were influenced by other variables: leadership, apparatus competence, awards, and the availability of work facilities.